The effect of sisal (Agave Sisalana) nanofiber in epoxy resin sealer on root canal obturation’s push-out bond strength - Astriani Amanda; Diatri Nari Ratih; Ema Mulyawati (Majalah Kedokteran Gigi Indonesia, 2021)
Sisal nanofiber can be used as an additional filler to increase the adhesion strength of the resin epoxy sealer. The aim of this study was to observe the effect of sisal nanofiber addition to epoxy resin sealer on push-out bond strength of root canal obturation material against the root canals. Twenty-five mandibular premolars (n= 25) were prepared until file F3 and obturated using 0%, 0.25%, 0.5%, 0.75%, and 1% sisal nanofiber sealer. After the specimens were stored at incubator, they were horizontally sectioned at apical third. Root sections were tested with push-out technique, and observed under a stereo microscope to determine the failure type. Data were analyzed with one-way ANOVA and LSD pos hoc at 95% confidence level (α=0.05). A one-way ANOVA test revealed that the addition of sisal nanofiber in epoxy resin sealer had a significant effect on the push out bond strength of the obturation material against the root canals. The failure type was observed predominantly in the cohesive type and the lowest in the adhesive type. The addition of sisal nanofiber to the epoxy resin sealer could increase the push-out bond strength of the obturation material against the root canals. Epoxy resin sealers with the addition of sisal nanofiber at a concentration group of 0.75% resulted in the highest push-out strength of root canal obturation materials followed by 0.5% concentration group.